Audits in a Textile Company and Advantages - Mine Seçkin; Feden Koç; Ahmet Çağdaş Seçkin (Acta Infologica)
Textile companies must develop strategies to survive in today’s competitive and volatile world and flexibly adapt these strategies to today’s conditions. In this competitive environment, audits conducted by an internal or external auditor, especially at the request of the customer, enable companies to differentiate themselves from other companies. Audits performed by companies can be classified in various ways. In this study, audit types are classified into internal and external audits depending on the type of auditor. If the audit is conducted by a person working in a company with a contract of pay, it is an internal audit, if not, it is an external audit. The principles and benefits of the audit to the company are explained in the study. In this study, a simulation was prepared to investigate the effect of audit frequency, internal interaction and number of employees in the company on the improvement of the company. In the prepared simulation, relevant changes were processed according to internal parameters on daily basis. As a result, it was found that with sufficient recovery of all parameters within the company, the highest improvement success is achieved when the audit frequency is conducted at least every 3 months. Future studies, information on how the developing information technologies and artificial intelligence provide convenience and perspective for audits are presented.